Production and quality of seeds in forage oats - Rodrigues, Luis Roberto de Andrade; Vieria, Roberval Daiton; Guimarães, Paulo Henrique Paiva (Pesquisa Agropecuaria Brasileira, 1993)
This research was carried out at the UNESP-Jaboticabal, SP, Brazil, to evaluate the production and quality of the seeds of the bristle oat (Avena strigosa Schreb) an of three cultivar of A. byzantina C. Kock., namely UFP2, UFP3, and UFP7. The seeds were harvested at 101 (T1); 121 (T2) and 128 (T3) days after sowing (DAS); and 77 days of regrowth of plants cut at 60 DAS (T4). The number of vegetative tillers did not change from 60 to 102 days of plant growth while the number (0.0 to 359.1) and the percentage (0.0 to 61.1%) of reproductive tillers increased. The bristle oat and the cultivars UPF2, UPF3, and UPF7, showed different seed productions (646; 1388; 1486; 1959 kg/ha). Seed productions in T1, T2, T3, and T4 were 1196; 1699; 1262; and 1327 kg/ha, respectively. Seeds of the bristle oat were of lower quality than the seeds of cultivars UPF2, UPF3 and UPF7 in all harvesting times. The seeds obtained in T2 and T3 presented higher germination and vigor when compared to those obtained in the other harvesting times.